PENERJEMAHAN ARAB, RIWAYATMU KINI (SEBUAH TINJAUAN SEJARAH) - Muhammad Yunus Anis (Arabic Literature Department, 2013)
This paper describes the history of Arabic Translations. There are three partsimportant things that correlated with Arabic Translations; (1) the history of terminologyamong terms of translations, (2) the definitions of translation it self based on a lot ofprofessionals scholarly, and (3) the history of “translation as a process” in Arabiclanguage from the earlier period of Islam. Finally, the result of data analysis shows thatthe process of Arabic translations comes from the process of trading in the Arabiancommunity with the strangers. In the other hands, the term of translation in Indonesianlanguage (terjemah) comes from Arabic language (tarjama-yutarjimu). It means thatthere are extremely correlations between Arabic Translation and Bahasa Indonesia. So,this is it the short history of Arabic Translations today.